2023
DOI: 10.7554/elife.81681
|View full text |Cite
|
Sign up to set email alerts
|

Early language exposure affects neural mechanisms of semantic representations

Abstract: One signature of the human brain is its ability to derive knowledge from language inputs, in addition to nonlinguistic sensory channels such as vision and touch. How does human language experience modulate the mechanism in which semantic knowledge is stored in the human brain? We investigated this question using a unique human model with varying amounts and qualities of early language exposure: early deaf adults who were born to hearing parents and had reduced early exposure and delayed acquisition of any natu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…Deaf individuals typically rely on sign language, or hearing devices to interact with other people. Consistent evidence suggests that sign language supports the proper development of language brain circuits in deaf participants (for recent evidence, see Cheng et al, 2023 ; Wang et al, 2023 ) and sign language proficiency is associated with higher executive functions (e.g., performance in Go/no‐go task, Simon task; Kotowicz et al, 2023 ). Although it has been suggested that knowing sign language can help deaf individuals to feel comfortable and less stressed in social contexts (La Grutta et al, 2023 ), sign language can only be used with other signing individuals and hearing aids and cochlear implants (CIs) may not always work efficiently (e.g., Orji et al, 2020 ).…”
Section: Introductionmentioning
confidence: 88%
“…Deaf individuals typically rely on sign language, or hearing devices to interact with other people. Consistent evidence suggests that sign language supports the proper development of language brain circuits in deaf participants (for recent evidence, see Cheng et al, 2023 ; Wang et al, 2023 ) and sign language proficiency is associated with higher executive functions (e.g., performance in Go/no‐go task, Simon task; Kotowicz et al, 2023 ). Although it has been suggested that knowing sign language can help deaf individuals to feel comfortable and less stressed in social contexts (La Grutta et al, 2023 ), sign language can only be used with other signing individuals and hearing aids and cochlear implants (CIs) may not always work efficiently (e.g., Orji et al, 2020 ).…”
Section: Introductionmentioning
confidence: 88%
“…In each run, there were 90 target word trials, each lasting for 2.5 s, as well as 14 catch trials, also lasting 2.5 s each. For more details about this experiment please see X. Wang et al (2023).…”
Section: Methodsmentioning
confidence: 99%
“…This set consisted of 40 concrete/object words and 50 abstract/nonobject words, the latter lacking explicit external referents. Participants were given instructions to visually examine each of these 90 target words, contemplate their meanings, and engage in an oddball one-back semantic judgment task (Wang et al, 2023).…”
Section: Stimuli and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations